SCAFFOLDING THE CREATIVE WRITING OF JENIUS WRITING STUDENTS - Elfa Eriyani; Yus rizal; Anggia Pratiwi (Universitas Negeri Makassar, 2021)
The purpose of this study was to discuss the scaffolding techniques used in the Jenius Writing (JW) program to support students’ creative writing. The Jenius Writing 58 (JW 58) class was studied using a qualitative case study method. The data were gathered through documentation from posts on the JW 58 WhatsApp Group and Gen JW International’s Facebook page. Data analysis was performed using Miles and Huberman’s data analysis technique, which included data reduction, data visualization, and conclusion drawing. The findings reveal four distinct types of creative writing scaffolding techniques: (1) writing inconsequentially, directly, or as things; (2) utilizing a hypnotic pattern or employing wording and phrases that can influence the development of writing; (3) employing a paragraph pattern to build writing, specifically writing based on the structure of words or phrases that focus on a single concept; and (4) using questions to develop a piece of writing.